2018
DOI: 10.1080/14767058.2018.1450858
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone – reference values and association with other bone metabolism markers in very low birth weight infants – pilot study

Abstract: The physiological range indicated by the measurements was close to the reference limits for adults (1-7 pmol/l; 9.4-66 pg/ml). PTH level above this range can be considered as hyperparathyroidism in preterm neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
4
12
0
1
Order By: Relevance
“…When the serum 25(OH)D 3 level was above 20 ng/mL, then no linear correlation between 25(OH)D 3 and iPTH levels was noted, which was consistent with the results of the study by Martins et al among Brazilians [46]. Matejek et al reported a significant relationship between iPTH and 25(OH)D 3 from the second month of life in healthy preterm newborns and that decreasing the 25(OH)D 3 level was accompanied by increasing iPTH [47].…”
Section: Discussionsupporting
confidence: 88%
“…When the serum 25(OH)D 3 level was above 20 ng/mL, then no linear correlation between 25(OH)D 3 and iPTH levels was noted, which was consistent with the results of the study by Martins et al among Brazilians [46]. Matejek et al reported a significant relationship between iPTH and 25(OH)D 3 from the second month of life in healthy preterm newborns and that decreasing the 25(OH)D 3 level was accompanied by increasing iPTH [47].…”
Section: Discussionsupporting
confidence: 88%
“…The reference range of plasma PTH in neonates is not well established. However, a recent study of 20 healthy preterm neonates (birth weight of 1000–1500 g, gestational age of 27–31 weeks) using third-generation chemiluminescence immunoassay demonstrated that the physiological range for PTH in neonates was close to the reference limits for adults (1–7 pmol/L; 9.4–66 pg/mL) 57. It is important to note that the trend in plasma PTH values is just as important as the absolute value, both for screening and monitoring.…”
Section: Introductionmentioning
confidence: 94%
“…However, a cross-reactivity to epimer described in the VIDAS method is residual, and the supplements from drops and additional sources in our study contain only the D3 form. Unfortunately, while choosing secondary outcomes, we did not include parathormone levels, which might be a sensitive indicator of calcium-phosphate balance based on recently published research [17,[42][43][44]. However, we included TRP and urinary calcium-creatinine ratios, which are sensitive markers of sufficient bone metabolism.…”
Section: Discussionmentioning
confidence: 99%